Exploration of Flip.id Application Usage with UTAUT2 and Perceived Credibility as a Mediator - Farah Nabilah; Alfi Alif; Muhammad Miqdad (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the factors affecting the use behavior of the Flip.id application using the UTAUT2 framework. The results indicate that performance expectancy, effort expectancy, and social influence positively affect behavioral intention. Meanwhile, facilitating conditions and behavioral intention positively influence use behavior. The study found that facilitating conditions and performance expectancy are the strongest antecedents in this research. The findings also reveal a negative effect of hedonic motivation on behavioral intention, while price value does not influence behavioral intention to use the Flip.id application. The moderation testing of experience on facilitating conditions and hedonic motivation shows a positive relationship. However, perceived credibility does not moderate the relationship between behavioral intention and use behavior. Based on the findings, it is evident that the ease of application use, adequate facilities, usefulness, and recommendations play crucial roles in increasing behavioral intention. Conversely, emotional and financial aspects do not demonstrate significant importance for users. This study provides implications for Flip application developers to enhance functional features, user education, and other facilities that support transaction processes within the application.